SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN AYAM BROILER SEHAT BERBASIS WEB: Information Systems;Web;HTML;and MySQL. - Megawaty, Merti; Suana, Irma; Febriyanto (JURNAL AKADEMIKA, 2022)
Putra West Sumatra is a family company engaged in the delivery of goods using land transportation. CV. With the increasing number of shipments of goods, problems often occur, this is because the company is still using a data system for shipping goods that has not been computerized. The purpose of this study is to design an information system for freight forwarding services at CV. Putra West Sumatra and modify it into a new system. The need for a new system input is recipient data, sender data, goods type data, delivery schedule data, and transaction data, the process needs to process sender data and process data for recipients who receive goods and payment reports to be sent according to the sender's schedule, the output needs namely the recipient data report, the sender data report, the goods data report and the payment data report. The result of this research is that the data processing of the delivery service can help effectively and reduce the risk of errors in data input and the collision of the delivery schedule.